Right parietal brain activity precedes perceptual alternation during binocular rivalry - Britz, Juliane (Hum Brain Mapp, 2010)
We investigated perceptual reversals for intermittently presented stimuli during binocular rivalry and physical alternation while the ongoing EEG was recorded from 64 channels. EEG topographies immediately preceding stimulus‐onset were analyzed and two topographies doubly dissociated perceptual reversals from non‐reversals. The estimated intracranial generators associated with these topographies were stronger in right inferior parietal cortex and weaker bilaterally in the ventral stream before perceptual reversals. No such differences were found for physical alternation of the same stimuli. These results replicate and extend findings from a previous study with the Necker cube and suggest common neural mechanisms associated with perceptual reversals during binocular rivalry and ambiguous figure perception. For both types of multi‐stable stimuli, the dorsal stream is more active preceding perceptual reversals. Activity in the ventral stream, however, differed for binocular rivalry compared to ambiguous figures. The results from the two studies suggest a causal role for the right inferior parietal cortex in generating perceptual reversals regardless of the type of multi‐stable stimulus, while activity in the ventral stream appears to depend on the particular type of stimulus. Hum Brain Mapp 32:1432–1442, 2010. © 2010 Wiley‐Liss, Inc.